(untitled) (Ibrahim Medical College Journal, 2009)
Background and Purposes: To observe the influence of parboiling, amylose content and gelatinization temperature of rice on plasma glucose and insulin responses in type 2 diabetic subjects because diabetic subjects are especially prescribed usage of starchy foods with low glycemic responses. Methods: Seventeen type 2 diabetic subjects ingested five test meals of 50g available carbohydrate as white bread, cooked rice with high (29%) and low amylose content (13%), undergoing different processing and gelatinization temperatures. The diets were taken in a random order after a 10h overnight fast with approximately 7 days interval as wash out period. Results: The glycemic index (GI) of all rice varieties were lower than that of white bread (p<0.001). Furthermore, GI of parboiled rice with a high amylose content was lower than that of parboiled low amylose rice (50±7 vs 71±5, p <0.01). No differences were observed between parboiled rice with high and low gelatinization temperature (50±7 vs 47± 4), nor between non-parboiled and parboiled rice (52±7 vs 50±7). Insulin responses to the five test foods did not differ significantly in the study subjects. Conclusions: In type 2 diabetic subjects the investigated rices were all low glycemic as compared to white bread, independent of parboiling and physico-chemical characteristics. The study showed that the amylose content, but not the gelatinization temperature, may be an useful criteria in selection of low GI rices irrespective of parboiling status. Ibrahim Med. Coll. J. 2008; 2(1): 12-16 Key words: Amylose, blood glucose, insulin, type 2 diabetes, parboiled rice. doi: 10.3329/imcj.v2i1.2925